Analysis the Implementation of Early Mobilization, Breast Care and Oxytosin Massage on Production ASI in Primipara Post Partum Mother in Dongko Health Centre Trenggalek City - Enggar Wahyu Anggraeni; Indasah Indasah; Koesnadi Koesnadi (Journal for Quality in Public Health, 2020)
The aim of the study was to analyze the effect of early mobilization, breast care and oxytocin massage on breast milk production in post partum mothers at the Dongko Health Center in Trenggalek Regency in 2018. The study was conducted at the Dongko Health Center in Trenggalek Regency on 12 November 2018 -8 December 2018. The type of association analytic research was the one group pre test - post test design model. Independent variables were early mobilization research, breast care and oxytocin massage, the dependent variable of breast milk expenditure in post partum mothers. The study population was all post partum mothers at the Dongko Health Center in Trenggalek Regency. The sampling technique used simple random sampling with a sample of 24 people. Data were analyzed using the Wilcoxon signed rank test and one way ANOVA. The results showed: 6 respondents (100%) before the early mobilization of ASI production was lacking, and after them normal, 6 respondents (100%) before breast care had less milk production and after them normal, 6 respondents (100%) before oxytocin massage had less milk production, and after them was normal. There is an effect of early mobilization, breast care and oxytocin massage on breast milk expenditure in post partum mothers where the value of p = 0,000 where p <α (0.05). Massage oxytocin has the highest mean value. This shows that the highest increase in breast milk expenditure in the Dongko Health Center in Trenggalek Regency is the oxytocin massage treatment. By doing oxytocin massage, the oxytocin reflex will increase and will work with the prolactin reflex in the formation of sufficient milk. Oxytocin will cause the muscle cells surrounding the milk making channel to contract or contract so that the milk is pushed out of the milk production channel and flows ready to be sucked by the baby